The effects of sea and road transport on physiological and electroencephalographic responses in Brahman crossbred heifers - Idrus, Zulkifli; Abubakar, Ahmed Abubakar; Sazili, Awis Qurni; Goh, Yong Meng; Imlan, Jurhamid Columbres; Kaka, Ubedullah; Sabow, Azad Behnan; Mohamed, Elmutaz Atta Awad; Othman, Azalea Hani; Raghazli, Razlina; Phillips, Clive J. C.; Hassan Nizam, Quaza Nizamuddin; et al. (MDPI, 2019)
The objective of the current study was to evaluate the effects of sea and road transport on the acute phase proteins (APP), cortisol, metabolic, haematological and electroencephalographic (EEG) responses of Brahman crossbred heifers. Sixty Brahman crossbred heifers were subjected to 14 d of transportation by sea from Darwin Port, Australia, to Pasir Gudang Port, Johor, Malaysia, and 330 km of road transportation. Results revealed that the intensity of response for most blood biochemical parameters increased significantly and were different from the baseline values taken while the animals were in Darwin Port, Australia. Haematological results obtained also revealed a significant increase and were different from the baseline values. Cortisol and APP (bovine alpha 1-acid glycoprotein and serum amyloid-A) values increased significantly and were different from the baseline values. Haematological parameters, APP, cortisol and EEG data (alpha, beta, delta and theta waves, total power and median frequency) decreased significantly following 4 and 7 days post-transport, suggesting a recovery of the animals from the stressfulness of transport. In conclusion, the current results revealed that the concentrations of biochemical and haematological parameters, cortisol, APP and EEG data were affected by both sea and road transport as evidenced by the significant changes recorded from the parameters above.